2013
DOI: 10.6000/1927-5129.2013.09.69
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Some Biological Seeds and Root Extracts of Plants Improves Fertility and Hatchability of Turkey Eggs

Abstract: An experiment was conducted to determine the fertility and hatchability of eggs laid by Turkey hens fed extracts of okra seed, pumpkin seed and guava root powder for 8 weeks. Twenty four, 32 weeks old turkeys (4 toms and 20 hens) were randomly selected and allotted into four treatment groups; T1 (No extract or feed supplementation); T2 (50 ml okra seeds extracts/ litre of water); T3 (50 ml guava root extract/ litre of water) and T4 (50 g pumpkin seed powder/kg of feed). Turkey hens were subjected to artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, Ebrahimi et al [59] reported that adding medicinal and aromatic plants to broiler rations did not affect mortality rates. It was concluded that the addition of some plant seeds and root extracts with antioxidant effects to the rations of breeder turkey hens improves fertility, hatchability and embryonic viability [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, Ebrahimi et al [59] reported that adding medicinal and aromatic plants to broiler rations did not affect mortality rates. It was concluded that the addition of some plant seeds and root extracts with antioxidant effects to the rations of breeder turkey hens improves fertility, hatchability and embryonic viability [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…In laying hens, there were no changes in the laying rate or the quality of the egg using pumpkin seed flour [81,82]. In the case of turkeys, the use of 5% of seeds in their diet improved the fertility of the eggs, reduced embryonic death, and increased hatching rate [83].…”
Section: Impact On Livestock Nutrition and Productivitymentioning
confidence: 99%
“…A study conducted by Machebe et al. () on supplementing diets of breeder turkey hens with some seeds and root extracts of plants concluded that okra and pumpkin seed extracts improved the fertility and egg hatchability traits of turkey hens (Badley, ). Subsequently, the turkey eggs showed low embryonic dead‐in‐shell: early (12%) and late (25%) compared to higher embryonic mortality in the control: 17% early and 50% late dead‐in‐shell embryos.…”
Section: Biochemical Modulatory Effects On Poultrymentioning
confidence: 99%